Characterization of xanthomonas spp. Strains by bacteriocins - Bonini, Marcel [UNESP]; Maringoni, Antonio Carlos [UNESP]; Neto, Julio Rodrigues (My University, 2007)
Twenty-five strains of Xanthomonas axonopodis pv. citri and 14 strains of Xanthomonas spp. were tested for bacteriocin production. X. axonopodis pv. passiflorae strains were sensitive to the bacteriocins produced by the 25 X. axonopodis pv. citri strains evaluated in this study while strains of X. axonopodis pv. manihotis and X. campestris pv. campestris showed variable sensitivity. Only five of the 25 X. axonopodis pv. citri strains were not inhibited by the bacteriocins produced by the two X. axonopodis pv. passiflorae strains. The bacteriocins produced by the Xanthomonas axonopodis pv. citri (FDC-806) and X. axonopodis pv. passiflorae (Mar-2850 A) strains were thermolabile, resistant to lysozyme and sensitive to DNAse. The bacteriocin produced by X. axonopodis pv. passiflorae was resistant to the action of proteinase K, trypsin and RNAse while the bacteriocin produced by X. axonopodis pv. citri was sensitive to these enzymes. The bacteriocins produced by X. axonopodis pv. passiflorae and X. axonopodis pv. citri were called passifloricin and citricin, respectively.
Caracterização de isolados de Xanthomonas spp. Por bacteriocinas
Keywords: Bacteria; Citrus canker